Estimating the biodiversity effects of structural adjustment in Ghana - Benhin, J.K.; Barbier, Bruno (2000)
A dynamic model of forest land use in Ghana is developed and used to derive demand equations for optimal timber harvesting, cocoa land and maize land that are a function of the model’s price parameters. An equation is also developed to estimate the biodiversity level in Ghana. The hypothesis that maize land expansion is a proximate cause of forest loss in either the pre or post-adjustment period is not supported by empirical results. Cocoa land expansion and timber expansion are significant factors, but their impacts on forest loss are reduced in the post-adjustment period. This infers that the Structural Adjustment Programme (SAP) has significantly reduced the impacts of cocoa land expansion and, less significantly, timber extraction on forest loss. In terms of price impacts on forest loss, relative timber input-output prices have the greatest impact on forest loss in both the pre and post-adjustment periods; adjustment policies have had little impact on the influence of timber prices on forest loss. The SAP, however, has affected the influence of cocoa and insecticide prices. Rising cocoa prices could induce farmers to convert forest land. Increasing the price of insecticides beyond a certain limit could also lead to increased rates of forest loss as farmers expand production by converting forest. The species-index estimates indicate that the rate of biodiversity loss has reduced in the post-adjustment period. It can be inferred that policies relating to prices and other incentives have reduced the rate of cocoa and maize land expansion and improved upon timber extraction.